Trilateration of location with celestial bodies using an android application - Sartin, Alexander Pacer (Nanyang Technological University, 2023)
The aim of this project is to pinpoint one’s coordinates with the use of celestial bodies through a mobile application. As accurate and consistent as the GPS is, there are some cases where GPS signals may be weak or inconsistent. Thus, relying on other forms of determining one’s location such as celestial navigation can be used instead of a GPS. By taking an image of the night sky, a user will be able to get their position. This is done so through the use of image processing algorithms, and celestial navigation formulas to derive the angular separation between the visible stars. The derived result will be compared with a database to determine the unknown celestial body, which allows us to use triangulation to find one’s location.